Analisis Pengaruh Format Penulisan Laporan terhadap Kecepatan Membaca Dosen di Universitas Ma Chung pada Media Kertas - Anggraeni, Risma Dwi Nur; Y, Hadi (Metris: Jurnal Sains dan Teknologi, 2018)
The issue of the environment has been a worldwide concerns. As an effort to solve this problem, then the development began to direct to sustainable development. In the education sector, these efforts have been implemented with the eco campus program. Therefore, experiment to engineer the new report writing format that can minimize paper usage is necessary. This experiment was conducted to determine the effect of factors of font size, leading, line length, and interaction between factors. In addition, it is performed to determine which treatment can produce the fastest reading speed response, but with the most efficient use of paper. In this experiment, the respondents were randomly assigned to one of the eight different combination of the level and factor with 12 pt or 10 pt (font size), 1 or 1.5 (leading), and A4 or A5 (line length).Then do the analysis of variance by using randomized block design to know the effect of the factors. Factors that significantly affect reading speed are the factor of font size as well as the interaction between the leading factor and the line length factor. This conclusion is reliable because the value of coefficient varience in this experiments is 18.22%.